2022
DOI: 10.3389/fpsyt.2022.836750
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Focused Anxiety Affects Behavioral Cardiac Risk Factors and Quality of Life: A Follow-Up Study Using a Psycho-Cardiological Rehabilitation Concept

Abstract: BackgroundHeart-focused anxiety (HFA) raises the risk for adverse outcomes in patients with heart disease. Despite this great importance, it is rarely assessed in clinical practice. Three dimensions are commonly defined in the context of HFA: heart-related fear, avoidance, and attention. The impact of these aspects on cardiac risk factors is essentially unclear. In this study, we investigated the relationship between HFA and behavioral cardiac risk factors as well as health-related quality of life (HRQoL), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 80 publications
0
9
0
3
Order By: Relevance
“…Furthermore, in study III, we observed that the more avoidance behaviour a patient experiences at the baseline of the intervention, the higher the likelihood of reducing cardiac anxiety with the help of iCBT. Previous research on cardiac patients has shown that increased avoidance behaviour at baseline negatively impacts physical activity levels (165) and is linked to a heightened risk of major adverse cardiac events (147). This underscores the importance of physical activity as protective against disabilities associated with NCCP (166), as well as the importance of motivating and supporting patients to participate in physical activity.…”
Section: Fear and Avoidance In Relation To Nccpmentioning
confidence: 95%
“…Furthermore, in study III, we observed that the more avoidance behaviour a patient experiences at the baseline of the intervention, the higher the likelihood of reducing cardiac anxiety with the help of iCBT. Previous research on cardiac patients has shown that increased avoidance behaviour at baseline negatively impacts physical activity levels (165) and is linked to a heightened risk of major adverse cardiac events (147). This underscores the importance of physical activity as protective against disabilities associated with NCCP (166), as well as the importance of motivating and supporting patients to participate in physical activity.…”
Section: Fear and Avoidance In Relation To Nccpmentioning
confidence: 95%
“…In einer weiteren Untersuchung erwies sich für die psychokardiologische Rehabilitation, dass herzbezogene Angststörungen das Erreichen von Therapiezielen im Bereich des gesundheitsförderlichen Verhaltens und der herzbezogenen Lebensqualität begrenzen. Dabei hatte vor allem das Vermeidungsverhalten als Komponente herzbezogener Ängste einen negativen Einfluss auf die mit der 6-Minuten-Gehstrecke erfasste körperliche Belastbarkeit, das körperliche Aktivitätsniveau und die körperbezogene gesundheitsbezogene Lebensqualität im SF-12 [10]. Die Zuweisung zu den Studiengruppen erfolgte entsprechend der Zuweisung zu den Behandlungssettings.…”
Section: Bisherige Evaluationsdatenunclassified
“…wesentlich schwerer vermittelbar und für die Patienten umsetzbar ist 8 . Angsterkrankungen erhöhen ebenfalls das kardiovaskuläre Risiko und die Mortalität 9 10 . Eine Posttraumatische Belastungsstörung (PTBS) durch ein Trauma in der Vergangenheit und besonders durch ein Ereignis im Rahmen der Herzerkrankung führt zu einem erhöhten kardiovaskulären Risiko und ist häufig mit einem metabolischen Syndrom (Übergewicht, Hyperlipoproteinämie, diabetische Stoffwechsellage, arterielle Hypertonie) assoziiert 11 12 .…”
Section: Kardiologie Und Psychosomatik Im Zusammenhangunclassified
See 1 more Smart Citation
“…In addition, recent studies show that CVD are closely related to the occurrence of psychological diseases such as anxiety and depression [10,11] , 15-20% of the patients display severe depressive disorders [12] . In Intensive Care Unit (ICU), the prevalence rate of anxiety, depression and post-traumatic stress disorder (PTSD) is 46%, 40% and 22% [13] .…”
Section: Introductionmentioning
confidence: 99%